Transposition of Branches of Radial Nerve Innervating Supinator to Posterior Interosseous Nerve for Functional Reconstruction of Finger and Thumb Extension in 4 Patients with Middle and Lower Trunk Root Avulsion Injuries of Brachial Plexus - 吴霞;丛小兵;黄启顺;艾方兴;刘玉田;鲁晓乘;李进;翁雨雄;陈振兵 (Current medical science, 2017)
This study aimed to investigate the reconstruction of the thumb and finger extension function in patients with middle and lower trunk root avulsion injuries of the brachial plexus. From April 2010 to January 2015, we enrolled in this study 4 patients diagnosed with middle and lower trunk root avulsion injuries of the brachial plexus via imaging tests, electrophysiological examinations, and clinical confirmation. Muscular branches of the radial nerve, which innervate the supinator in the forearm, were transposed to the posterior interosseous nerve to reconstruct the thumb and finger extension function. Electrophysiological findings and muscle strength of the extensor pollicis longus and extensor digitorum communis, as well as the distance between the thumb tip and index finger tip, were monitored. All patients were followed up for 24 to 30 months, with an average of 27.5 months. Motor unit potentials（MUP） of the extensor digitorum communis appeared at an average of 3.8 months, while MUP of the extensor pollicis longus appeared at an average of 7 months. Compound muscle action potential（CMAP） appeared at an average of 9 months in the extensor digitorum communis, and 12 months in the extensor pollicis longus. Furthermore, the muscle strength of the extensor pollicis longus and extensor digitorum communis both reached grade Ⅲ at 21 months. Lastly, the average distance between the thumb tip and index finger tip was 8.8 cm at 21 months. In conclusion, for patients with middle and lower trunk injuries of the brachial plexus, transposition of the muscular branches of the radial nerve innervating the supinator to the posterior interosseous nerve for the reconstruction of thumb and finger extension function is practicable and feasible.